Measurement of physical activity in children and adolescents with cerebral palsy: the way forward. (25th June 2013) - Mitchell, Louise; Ziviani, Jenny; Boyd, Roslyn
Abstract : This commentary is on the original article by Maher et al. on pages827–833 of this issue.